Typical symptoms of Body Dysmorphic Disorder (BDD) in patients seeking preventive and corrective medical-aesthetic treatments: analysis of differences and potential predictors - Donatelli, Chiara; Centofanti, Domenico; Bartoletti, Emanuele; Cerea, Silvia (Aesthetic Medicine, 2025)
Background: Body dysmorphic disorder (BDD) is a condition characterized by excessive concern for perceived physical defects, often associated with the demand for medical aesthetic treatments. However, psychological differences between patients seeking preventive or corrective treatments and possible predictors of BDD remain unclear. Aim: This study analyzed symptomatic and behavioral differences between patients requesting preventive and corrective medical aesthetic treatments, assessing the presence of typical BDD symptoms and possible predictors to improve screening, reduce inappropriate treatments, and optimize clinical approaches. Methods: A total of 136 participants completed online self-report questionnaires investigating demographic and anamnesis data and motivations for medical aesthetic treatments. The COPS, MAIA, IACS, and E-pgm questionnaires assessed BDD symptomatology, body perception, social media comparison, and post-procedure expectations. Results: Among participants, 56.6% belonged in the corrective group, while 43.4% were in the preventive group. The corrective group had significantly higher scores in COPS (p = 0.01), social media comparison (p = 0.001), and post-treatment expectations (p = 0.01), whereas the preventive group showed higher body confidence (p = 0.05). In the preventive group, BDD correlated with social media comparison (r = 0.575, p < 0.001) and post-treatment expectations (r = 0.403, p = 0.004), whereas in the corrective group, BDD correlated with age, body perception, dissatisfaction, self-esteem, and post-operative expectations (p < 0.001). Conclusion: In the preventive group, social media comparison was the only predictor of BDD, while in the corrective group, age, body perception, and social media comparison were significant predictors. BDD is often underdiagnosed and may lead to post-treatment dissatisfaction. A thorough screening of expectations and psychological characteristics could reduce the risk of inappropriate interventions, improving selection criteria for medical aesthetic treatments and patient satisfaction.